Structural anomaly of chromosome 18 with Edward syndrome phenotype - Krishnamurthy, B.; Savitha, M. R.; Patil, Pratibha (International Journal of Contemporary Pediatrics, 2017)
Edward syndrome has a median survival time of 14.5 days. Importance of this case report is in the rarity of this karyotype and prolonged survival as compared with complete trisomy 18. A 5-year-old male child with global developmental delay had brachycephaly, microstomia, narrow palatal arch, low set ears, widely spaced nipples, diastasis recti, bilateral cryptorchidism, ulnar deviation of both hands with absent distal creases, rocker bottom foot with overlapping of second and third toes. Cardiac, ophthalmological, otolaryngological evaluations, ultrasonography abdomen, and skeletal survey were normal. Computed tomography head showed mild dilatation of lateral ventricles. Karyotyping revealed 46 chromosomes with an asymmetry of chromosome 18. Pathognomonic segment responsible for Edwards phenotype is in the q arm of chromosome 18. In this patient, there was no complete trisomy 18. However, there was an abnormality in the form of asymmetry that can be due to either isochromosome 18q, translocation chromosome 18 or duplication of the critical region.